A Flourishing Brain in the 21st Century: A Scoping Review of the Impact of Developing Good Habits for Mind, Brain, Well‐Being, and Learning. Issue 1 (23rd November 2021) - Ekman, Rolf; Fletcher, Anna; Giota, Joanna; Eriksson, Axel; Thomas, Bertil; Bååthe, Fredrik
ABSTRACT: Emerging scientific knowledge such as the role of epigenetics and neuroplasticity—the brain's capability to constantly rewire with every action, experience, and thought—is fundamentally changing our understanding of the potential impact we can have on our brain. Our brain is formed by our habits in interaction with our body, the environment, influenced by our lifestyle, successes, failures, and traumas. Neuroplasticity proves that every student's brain is a work in progress, and it is never too late to take better care of one's cognitive fitness. This review presents a repertoire of good habits (GHs). Combined, we suggest that these GHs provide conditions for optimal brain health, by acting as a "Mental Vaccine" which enhances the brain's resilience to brain health‐degrading challenges. We argue that schools have a crucial role to play in empowering students to increase their own stress resilience, well‐being, and learning by developing their own GHs profile. LAY ABSTRACT: Which good habits have been found to impact the adolescent's development? The following good habits were chosen from recent research: (1) healthy eating, (2) exercising, (3) rest and sleep, (4) optimism, (5) managing stress, (6) making autonomous decisions, (7) variety and challenges, (8) social interactions with friends, (9) learning new things, and (10) repetition. This article presents scientific work on good habits with influence on the adolescent's well‐being, mind, brain, and lifelong learning.